THE PARADIGM OF SCIENCE ACCORDING TO SUHRAWARDI AL MAQTUL - Faishol, Riza; Riduan, Imam Malik; Fauzi, Anis; Nasrodin, Nasrodin; Hamdanee, Sayyed Ahmad (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
Science and knowledge are two important things to study. Suhrawardi was a first generation of sufi philosophers. Using the hermeneutics method, the author focuses the study on how the concept of science is in the perspective of Suhrawardi Al Maqtul. From the discussion carried out, it was concluded that in the illumination theory proposed by Suhrawardi, one of the methodologies for obtaining high knowledge was to practice known science as corroborated by the postulates in the Quran and Hadith. According to Suhrawardi, to obtain light, man must move to draw closer to that light with science and charity.